Design And Analysis Of Discrete High Slew Rate Low Noise Voltage Regulator For RF Transceiver System - Mohamad Noor, Mardiana (Universiti Sains Malaysia, 2005)
Communication system consists of various circuits and having a good and regulated source is crucial in order to get the desired signals at the output. The common problems in getting such good sources are spikes, ripple and fluctuating DC input. Linear voltage regulator is a source circuit to supply a steady, constant output. In addition to its basic function, an attempt to implement its usage in the radio frequency circuits has been made through out this project. Three regulator circuits have been designed, which are negative voltage regulator, positive voltage regulator and ripple rejection voltage regulator. The basic schematics for these circuits were implemented from two types of integrated chips; LM317 and µA723. The positive voltage regulator is used to detect positive peak of ripple input voltage and negative voltage regulator performs vice versa task. Ripple rejection voltage regulator acts as an auto-ripple rejecter circuit, which will reject the ripple detected by positive and negative voltage regulators and supply smooth and constant input to the next circuitry. As the gain of the ripple rejection voltage regulator is very small compared to the input voltage, this regulator also can be applied in the gain compression circuit. Those circuits designed in this project are direct transformation from the schematics used in the low frequencies to the design using microstrips for RF circuits.